2021
DOI: 10.1002/srin.202100376
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Fracture Characteristics of Heat‐Affected Zone in Shipbuilding Steel Plates with Mg Deoxidation after High Heat Input Welding

Abstract: To clarify the microstructure and fracture characteristics of heat‐affected zone in shipbuilding steel plates with Mg deoxidation after high heat input welding, two steels with 0.0002 (2Mg) and 0.0049 (49Mg) wt% Mg are prepared and investigated with metallography and crystallography. Compared with 2Mg, TiN particles are incrementally refined in 49Mg, making the prior austenite grain (PAG) size decrease. In the large‐sized grains of 2Mg, there are preferentially formed coarse grain boundary ferrites (GBFs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Consequently, with 0.0022 wt% B addition, GBFs and FSPs reduce, followed by IAFs increasing with the higher deformation ability (KAM maps in Figure 2f) and larger HAGB density (grain boundary distribution maps in Figure 2e), which can significantly improve the ability to barrier the crack nucleation and propagation. [ 15 ] The HAZ toughness at −40 °C is thereby greatly improved from 40 to 141 J (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, with 0.0022 wt% B addition, GBFs and FSPs reduce, followed by IAFs increasing with the higher deformation ability (KAM maps in Figure 2f) and larger HAGB density (grain boundary distribution maps in Figure 2e), which can significantly improve the ability to barrier the crack nucleation and propagation. [ 15 ] The HAZ toughness at −40 °C is thereby greatly improved from 40 to 141 J (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Our previous industrial tests and laboratorial studies revealed that the oxide metallurgy technology with Mg deoxidation can effectively enhance the HAZ toughness of steel plates after HHIW by refining the austenite grains or promoting the ductile microstructures. [13][14][15][16][17][18] The effect of B addition on the mechanical properties of HAZ has been studied by several DOI: 10.1002/srin.202200102…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the prior-austenite grains (PAGs) of post weld steel are coarsened seriously reducing the low-temperature toughness of CGHAZ. [3][4][5] Considering the application environment of the shipbuilding steel plates, the low-temperature impact toughness plays a crucial role.…”
Section: Introductionmentioning
confidence: 99%
“…The oxide metallurgy technology with strong deoxidizers, such as Mg, has been widely reported to improve the HAZ toughness of thick steel plates by refining austenite grain sizes or promoting intragranular acicular ferrites (IAFs). [ 7,8 ] In our previous industrial tests and laboratorial studies, it was shown that the excellent HAZ toughness of shipbuilding steel plates can be obtained with 0.0010–0.0099 wt% Mg addition. [ 9–11 ] The CGHAZ microstructures for high‐strength offshore engineering steels present the bainite feature.…”
Section: Introductionmentioning
confidence: 99%